Caracterização genotípica de cordeiros mestiços Texel para genes associados com a qualidade de carne - ALINE APARECIDA DA SILVA MIGUEL (2023)
The identification of sheep carrying polymorphisms associated with characteristics of economic interest in animals can be an interesting strategy in the agricultural sector. Therefore, the objective was to identify polymorphisms associated with meat quality in a herd of Texel crossbred lambs (offspring of Texel breeders with SRD females). The lambs (n=51) were weaned at 90 days and received protein-energy supplementation formulated to achieve an average daily weight gain of 300 g. At 120 days, the lambs were slaughtered and Longissimus dorsi muscle samples were collected for meat quality analysis and gentotype characterization. Polymorphisms were observed in the CAST gene, resulting in three genotypes (MM, MN and NN) in the studied population. Lambs of the MM genotype showed less exudate loss during slaughter, losing two percentage points less water compared to the other genotypes. In the DGAT-1 gene, two genotypes were identified (CC and CT), with the CT genotype being associated with higher birth weight, with an average increase of 0.89 kg compared to the CC genotype (p<0.05). Furthermore, lambs with the CC genotype demonstrated greater subcutaneous fat thickness, with an increase of 0.41 mm (p<0.05). Regarding the LepR gene, no polymorphisms were found (p<0.05), with all animals in the herd characterized by the CC genotype. Keywords: beef sheep farming, polymorphism, molecular markers, CAST, DGAT1, LepR